2006
DOI: 10.1158/1078-0432.ccr-05-2820
|View full text |Cite
|
Sign up to set email alerts
|

Local Targeting of Malignant Gliomas by the Diffusible Peptidic Vector 1,4,7,10-Tetraazacyclododecane-1-Glutaric Acid-4,7,10-Triacetic Acid-Substance P

Abstract: Purpose: Malignant glial brain tumors consistently overexpress neurokinin type 1 receptors. In classic seed-based brachytherapy, one to several rigid 125 I seeds are inserted, mainly for the treatment of small low-grade gliomas. The complex geometry of rapidly proliferating high-grade gliomas requires a diffusible system targeting tumor-associated surface structures to saturate the tumor, including its margins. Experimental Design: We developed a new targeting vector by conjugating the chelator 1,4,7,10-tetraa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 39 publications
2
112
0
13
Order By: Relevance
“…Figure 2D shows a case of glioblastoma coexpressing both receptors. Because of the blood-brain barrier, a successful targeting strategy with substance P analogs does not consist in a systemic application but in a local application into the tumor or in the cavity left by the resected tumor (31). Although substance P analogs were successfully applied in vivo in glioblastomas, NPY analogs have never been tested in glioblastomas.…”
Section: Glioblastomasmentioning
confidence: 99%
“…Figure 2D shows a case of glioblastoma coexpressing both receptors. Because of the blood-brain barrier, a successful targeting strategy with substance P analogs does not consist in a systemic application but in a local application into the tumor or in the cavity left by the resected tumor (31). Although substance P analogs were successfully applied in vivo in glioblastomas, NPY analogs have never been tested in glioblastomas.…”
Section: Glioblastomasmentioning
confidence: 99%
“…At-MX35-F(ab') 2 Cancer des ovaires 9 patients traités ; aucune toxicité significative [31] 213 Bi-Substance P Glioblastome 5 patients traités ; 2 améliorations de l'index de Barthel [32,33] TIRÉS À PART J. Ménager …”
Section: Anticorps Radiomarquéunclassified
“…Internalization of substance P conjugated to the chelator 1-(1-carboxy-3-carboxypropyl)-1,4,7,10-tetraazacyclododecane-4,7,10-triacetic acid (DOTAGA) was found to be specific, and in a first clinical study using 90 Y-and 213 Bilabeled DOTATAGA-substance P, 20 patients have been enrolled (116). Patients with high-grade lesions (n 5 16) were included after progression of disease or denial of conventional treatment options.…”
Section: Radiolabeled Substance P and Chloratoxinmentioning
confidence: 99%
“…On the basis of these encouraging results, 2 further studies were initiated with radiolabeled substance P. The previous study (116) showed that from a surgical point of view, resectability was facilitated by improved demarcation and by the radiation-induced antiangiogenic effect in these patients who had been treated up front with locoregional radiopeptide therapy. Therefore, a study (118) analyzed whether neoadjuvant treatment before tumor resection is also a valid concept for improved therapy of malignant brain tumors.…”
Section: Radiolabeled Substance P and Chloratoxinmentioning
confidence: 99%